Double CRISPR knockout of pectin degrading enzymes improves tomato shelf‐life while ensuring fruit quality - Isabel Ortega‐Salazar; Daphne Crum; Adrian O. Sbodio; Yuko Sugiyama; Adam Adaskaveg; Duoduo Wang; Graham B. Seymour; Xueqi Li; Selina C. Wang; Barbara Blanco‐Ulate (Plants, People, Planet, 2024)
Social Impact Statement Tomato fruit is an important and popular commodity producing $95.62 billion worldwide. Tomato fruit losses in the supply chain vary between 25% and 42% depending on the production area and the availability of postharvest technologies. For many decades, conventional tomato breeding programs have focused on extending the shelf‐life of fresh‐market varieties. However, in many instances, consumer‐based quality traits were not considered a priority. Consumers are now demanding safe, nutrient‐rich, high‐flavor, and convenient fruit. Here, we demonstrate the use of gene editing to improve fruit shelf‐life and positively impact quality, which can help significantly reduce tomato fruit losses and meet consumer expectations. Summary Finding alternative ways to extend tomato fruit shelf‐life without reducing the quality is critical to ensure the accessibility and likeability of this commodity worldwide. Improving fruit firmness in tomato fresh‐market varieties directly impacts their shelf‐life potential. We simultaneously knocked out two pectin‐degrading enzymes, polygalacturonase (SlPG2a) and pectate lyase (SlPL), key for tomato fruit softening. We expected this gene‐editing approach to result in longer‐lasting fruit without negatively impacting consumer‐based quality attributes. By generating the double clustered regularly interspaced short palindromic repeats (CRISPR) knockout PGPL, we evaluated the combined functions of SlPG2a and SlPL on fruit quality, including shelf‐life attributes like firmness and water loss, fruit marketability, and disease incidence. We also assessed additional attributes impacting consumer acceptance, such as taste and aroma. We revealed that the enzymes SlPG2a and SlPL act additively, significantly impacting fruit firmness and shelf‐life, with the double CRISPR knockout PGPL outperforming the wild‐type fruit. Additionally, fruit quality traits, such as sugar: acid ratio, aroma volatiles, and skin color, were improved or not affected in the double CRISPR knockout PGPL compared to the wild‐type. The discoveries of this research provide new insights into the influence of pectin backbone degradation on fruit physiology and postharvest quality, which can be used in crop improvement programs to make fruit more resilient in the supply chain without compromising quality.